Optimization of fluid characteristics of 2D materials for inkjet printing. Issue 30 (28th July 2016) - Michel, Monica; Desai, Jay A.; Delgado, Alberto; Biswas, Chandan; Kaul, Anupama B.
ABSTRACT: 2D materials have shown to be the next step in semiconductor use and device manufacturing that can allow us to reduce the size of most electronics. One of the novel ways to obtain 2D materials is through liquid exfoliation, in which these materials can be obtained by dispersing the smallest possible particles in different solvents. Once obtained, the solutions can be used to manufacture devices via different processes, one of which is inkjet printing. This process relies in selecting "jettable" fluids, which need to have the necessary combination of viscosity and surface energy or "wettability". In this work we have modified the viscosities and surface energies of five solvents: IPA (Isopropanol), NMP (N-methyl – 2 pyrrolidone), DMA (Dimethylacetamide), DMF (Dimethylformamide) and a mixture of Cyclohexanone / Terpineol 7:3. We have found an avenue to tailor the viscosity of these solvents though the addition of Ethyl Cellulose (EC), where the viscosity has been increased by up to 15 times at an EC concentration of 6%. For inkjet printing, ideally a viscosity of 4 – 10 cP is recommended, which we have been able to achieve with all of the solvents studied. It has been found that the different solvents present different susceptibilities to the EC addition, with DMA and DMF being the least sensitive to the EC addition. We have also studied the change in the drop dynamics and interactions of the 2D solutions with the substrate. Through this analysis we have found solvents that appear to be attractive for inkjet printing of MoS2 and graphite.